(untitled) (Journal of Psychiatrists’ Association of Nepal, 2026)
Introduction Sleep disturbances represent a core symptom cluster in Major Depressive Disorder (MDD), profoundly affecting patient prognosis, daily functioning, and overall quality of life. Characterizing the patterns and severity of sleep issues within MDD populations is vital for optimizing clinical management strategies. This study aimed to comprehensively evaluate the prevalence, and clinical correlates of disturbance in sleep quality among adult MDD patients attending psychiatry OPD at Birat Medical College and Teaching Hospital (BMCTH), with a particular focus on the relationship between sleep quality and depression severity. Material and methods A descriptive, cross-sectional study design was employed. Data collection occurred over a 1-year period (August 2023 - July 2024) within the Department of Psychiatry. Utilizing purposive sampling, 110 adult out-patients meeting DSM-5 criteria for MDD were enrolled. Information was gathered using a structured proforma for socio-demographic and clinical details, the Hamilton Depression Rating Scale (HDRS) for assessing depression severity, and the Pittsburgh Sleep Quality Index (PSQI) for evaluating subjective sleep quality over the preceding month. Statistical analyses included descriptive statistics, independent t- tests, Pearson’s correlation, and multiple linear regression. Results The study cohort (N=110) had a mean age of 38.5 ± 11.5 years, comprised equally of males and females (50% each). The average duration of the current illness episode was 9.1 ± 4.2 months. A striking 78.2% (n=86) of patients reported poor sleep quality, defined by a PSQI global score > 5. The sample’s mean global PSQI score was 12.8 ± 4.5, signifying substantial disturbance in sleep quality. A strong positive correlation emerged between PSQI global scores and HDRS total scores (r = 0.68, p= 0.001). Multiple linear regression identified HDRS score as a robust predictor of poorer sleep quality (β = 0.68, p =0.001), explaining a significant portion of the variance (Adjusted R² = 0.493). Age, gender, and duration of illness did not significantly predict PSQI scores in this model. Conclusion Poor sleep quality is present among adult MDD out-patients. Significant association between sleep quality disturbance and depression severity could be established.